Pengaruh Stres Kerja dan Cyberloafing terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada PDAM Payakumbuh - Kevin Maulana; Jhon Very; Chintya Ones Charli (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to determine the effect of Job Stress and Cyberloafing on employee performance with Job Satisfaction as an intervening variable at PDAM Payakumbuh. The method used is quantitative and the sampling method uses saturated sampling at PDAM Payakumbuh. The results of this research found that work stress has a significant positive effect on job satisfaction, Cyberloafing has no significant positive effect on job satisfaction, Job stress has a significant positive effect on employee performance, Cyberloafing has no significant positive effect on employee performance, Job stress has a significant positive effect on employee performance through Job Satisfaction, Cyberloafing has no significant positive effect on employee performance through job satisfaction at PDAM Payakumbuh.